Implementasi Pengolahan Citra Digital Untuk Mendeteksi Terjadinya Gol Pada Pertandingan Futsal Menerapkan Metode BLOB - Cornardus Jenius Priska Ziraluo (Journal of Computer System and Informatics (JoSYC), 2020)
The referee is what determines the occurrence of violations that occur in the match and also determines the occurrence of goals or not the occurrence of goals in the goal in determining that the referee must take a very fair decision so as not to harm one of the competing teams and the referee also has weaknesses and can make decisions which can be detrimental to one of the teams, maybe we often see in futsal matches mistakes that occur in the field but the referee doesn't know it, like a ball that has crossed the goal line and entered the goal is pulled back by the player but the referee doesn't know it because the referee's view is blocked by the player. Digital image is a picture of an analog object in the form of video signals on a television monitor as segmentation, calculation, detection, and tracking and recognition. In this case the digital image will detect the goal in the goal through several processes before detecting. By using the morphology of dilation and erosion images, detection of the ball entering the goal can be detected, detecting the ball into the goal using the BLOB method, in this case the digital image will be able to detect an object whether or not. Blob or blob detection method is detecting a collection of pixel dots that have different colors (lighter or darker)